Public Participation, Transparency- The Utilisation of Social Media Bandung City - ARWANTO ARWANTO (Jurnal Studi Pemerintahan, 2018)
The Mayor of Bandung, Ridwan Kamil, has reformed his government. It is now the best performing city in Indonesia, and mainly through the use of technology such as social media. This paper focuses on the use of his social media account to increase transparency and public participation. This paper answers questions about: how he utilised his Facebook account to be open and involved his electorate and maximize government efficiency and responsibility. This research uses a mixed qualitative and quantitative content analysis to answer research questions. The data are consists of 264 posts from January 2016 to June 2016, and are categorised as: information sharing, government activity, decision impacts, accountability, and personal posts. The results show that Ridwan Kamil Facebook page became a venue for two-way interaction between the public and government. In term of transparency, Facebook can provide information that is accessible to the people. This research found that the selection of issues and language style of the posts have significant impacts on the level of public engagement. In addition, it highlighted the potential of the use of social media to promote the branding of individuals and corporation including government.